Peningkatan Usaha UMKM Melalui Penambahan Wawasan Tentang Usaha Kreatif di Jepang - Nursasi, Enggar; Bunyamin, Bunyamin; Munfaqiroh, Siti; Mauludin, Hanif; Wiyarni, Wiyarni; Rahmania, Benita (STIE Malangkucecwara, 2025)
The purpose of this community service activity is to help micro, small, and medium enterprises (MSMEs) grow and improve, as well as to provide motivation for them to be more creative in developing their businesses. Small business initiatives in Pringgodani Village, Bantur District, Malang Regency have progressed rapidly, achieving a 25% increase in 2024. The community service program was carried out by involving a resource person from Japan, Miyu Uehara, a Japanese student who motivated MSME actors by presenting examples of home-based businesses in Japan that are rich in creativity and innovation. Meanwhile, a graduate student from STIE Malangkucecwara, Edi Purnomo, provided support from the perspective of local government in his role as Subdistrict Head.The activity continued with an explanation of marketing support facilities delivered by the head of the Bantur District MSME association, Mr. Arik Dwi Asmara, who emphasized the importance of product quality to attract consumers and the need for continuous innovation to ensure long-term business sustainability.